2003
DOI: 10.1557/proc-807-459
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Copper in 1 M NaCl under Strictly Anoxic Conditions

Abstract: %675$&7The corrosion of copper in 1 M NaCl has been investigated at room temperature and at 80 o C by an on-line resistance probe, solution analysis of dissolved copper and weight loss measurements. At room temperature, corrosion of the copper as indicated by an increase of the probe resistance has been detected during the first 60-80 h of exposure. After the corrosion potential has reached the immunity region of Cu, a decrease in the resistance of the sensor is observed, probably due to redeposition of Cu fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…The diffusion contribution presented in the model given as Figure 7(d) may be attributed to the deposition of copper, as shown in Figure 6. This hypothesis is supported by Bojinov et al, 29 who observed back deposition of copper. As the measured frequency range was insufficient to allow determination of the diffusion time constant, the diffusing species could not be identified.…”
Section: Table III Kinetic Parameters Used For the Simulation And Res...supporting
confidence: 58%
See 1 more Smart Citation
“…The diffusion contribution presented in the model given as Figure 7(d) may be attributed to the deposition of copper, as shown in Figure 6. This hypothesis is supported by Bojinov et al, 29 who observed back deposition of copper. As the measured frequency range was insufficient to allow determination of the diffusion time constant, the diffusing species could not be identified.…”
Section: Table III Kinetic Parameters Used For the Simulation And Res...supporting
confidence: 58%
“…In an earlier study, Bojinov et al used an on-line resistance probe to discover that copper corroded at an appreciable rate of 16 μm/y during short-time exposure to 1 M NaCl that contained very small amounts of oxygen. 29 After longer exposure, the corrosion rate decreased and back-deposition of copper was reported. As part of the analysis of the suitability of copper for nuclear waste storage, Sharifi-Asla and Macdonald 30 have performed studies of the hydrogen evolution reaction on copper in deoxygenated neutral aqueous borate buffer solutions.…”
mentioning
confidence: 99%
“…6,7 In spite of the existence of several papers that demonstrate the lack of corrosion of Cu in anoxic water and chloride containing solutions, [8][9][10] there is still a need to determine if the hydrogen liberated during interaction of copper with deoxygenated water is the product of sustained corrosion of the material. The present paper aims at verifying a working hypothesis proposed in earlier work 11 that upon immersion in a neutral aqueous solution, a mixed Cu (I)-Cu (II) oxide-hydroxide is formed on Cu during the oxic phase. In addition, soluble Cu (I) is supposed to be oxidized to soluble Cu(II) by the residual oxygen in a homogeneous reaction.…”
supporting
confidence: 65%
“…Attempts to study this system have employed either sensitive measurements of the change in electrical resistance or careful measurements of the amount of hydrogen gas produced. [9][10][11] Not unexpectedly, there could be disturbances in the results by residual oxygen and hydrogen emanating from other sources, for example, from within the copper itself. [12] Extrapolations of corrosion rates for very long times, up to a million years, are very sensitive to even small changes in the reaction rates; therefore, other means of bounding the corrosion extent for the postclosure safety assessment are preferred.…”
Section: Introductionmentioning
confidence: 99%